Strategi Peningkatan Kinerja Instalasi Farmasi Rumah Sakit PKU Muhammadiyah Wonosobo dengan Pendekatan Balanced Scorecard pada Perspektif Pelanggan - Sri Wahyuningsih (STIKes Ibnu Sina Ajibarang, 2024)
Hospital Pharmacy Installations (IFRS) have an important role in providing services to patients which generally contribute the highest income in hospitals. The wide role of IFRS in the smooth running of health services as the largest source of income in hospitals means that an IFRS development strategy needs to be carried out in the face of competition with other hospitals. This research aims to determine the results of measuring the performance of the PKU Muhammadiyah Wonosobo hospital's pharmaceutical installation using the Balanced Scorecard approach from a customer perspective and to provide suggestions for performance improvement strategies based on the results of these performance measurements. Performance measurement in this research uses a Balanced Scorecard approach from a customer perspective.The results show that from a customer perspective, patient satisfaction shows that patient results are satisfied, patient growth is 13.96% (increased) but prescription networkability is 81.50% (decreased). Recommended strategies for improving IFRS PKU Muhammadiyah Wonosobo performance are carried out by increasing indicators from the customer perspective in the Balanced Scorecard, including indicators for recipe networkability.